Kaji Perbandingan Karakteristik Respon Dinamik Suspensi Sepeda Motor dengan Memakai Peredam Viscous Oli Sintetis dan Minyak Nabati - N Nusyirwan (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
The motorcycle is a vehicle which is widely used by people today, especially in the narrow streets. This vehicle is able to meet the needs of users because it is cheap, fuel-efficient is also very dynamic to reach places that are difficult to reach by four-wheeled vehicles that have large dimensions. In addition to the many advantages of two-wheeled vehicles should also be taken into account in terms of comfort and safety. Safety factor will depend on many factors, other than humans as a rider, vehicle reliability and the quality level of the road is an important safety factor. Factors vehicle will be in direct contact with the road in its path. Regarding the main factor for the safety of the road is how the vehicle is still stable when it fell into a deep hole or a very rough road. Suspension as one of the main tools to respond to the shock loads on a motorcycle is the main factor that should be taken into account. Types of suspension are used to reduce response style and shock will be felt directly by passengers. This is one study which the suspension is an extremely important characteristic studied. One that plays a role in the election of a suspension damper oil. Oil damper as viscous dampers shock loads can convert into friction and heat. Viscous good silencer is to transfer mechanical energy into heat as much as possible, without changing the characteristics of the damper oil itself. Oils tested, there are three types of commercial oil  chosen by the suspension manufacturers. This study was conducted to replace oil with vegetable oil palm oil CPO output can reduce the amplitude of 9.2 cm for shock loads of 20 kg with a height of fall of 3 m. Fall height of 3 m damping ratio of vibration  damper formed by CPO was 0.41.